Renal artery aneurysm: An endovascular treatment for a rare cause of hypertension - Moreira, N (2012)
Renal artery aneurysms are a rare cause of secondary hypertension. Endovascular treatment with a polytetrafluoroethylene (PTFE)-coated stent can exclude aneurysms and treat hypertension. We report the case of a 23-year-old man with hypertension diagnosed three years earlier and in whom renal angiography revealed three aneurysms involving the right renal artery. A covered stent was implanted, resulting in successful exclusion of the aneurysm. Ten months after the procedure the patient is asymptomatic and with normal blood pressure without antihypertensive therapy.